2003
DOI: 10.1046/j.1468-2982.2003.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Migraine in Narcoleptic Patients: A Confirmatory Study

Abstract: Previously we have reported an increased prevalence of migraine in narcoleptic patients. Because of the theoretical and clinical implications of this finding we recruited an independent new study sample of 100 patients with proven narcolepsy and conducted a structured 26-item interview based on the international diagnostic criteria for headache disorders, the Kiel Headache Questionnaire. Narcolepsy symptoms were measured by means of the Stanford Centre for Narcolepsy Sleep Inventory. Migraine prevalence was tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 30 publications
2
64
1
2
Order By: Relevance
“…The prevalence of migraines is greater in the narcoleptic subpopulation with more intense symptoms. 43,44 8) Narcolepsy and multiple sclerosis Narcolepsy and multiple sclerosis (MS) are both commonly associated with mutations of the HLA 0602 allele, and both are considered autoimmune disorders. Multiple sclerosis is a risk factor for narcolepsy, but the opposite is not true.…”
Section: ) Migrainementioning
confidence: 99%
“…The prevalence of migraines is greater in the narcoleptic subpopulation with more intense symptoms. 43,44 8) Narcolepsy and multiple sclerosis Narcolepsy and multiple sclerosis (MS) are both commonly associated with mutations of the HLA 0602 allele, and both are considered autoimmune disorders. Multiple sclerosis is a risk factor for narcolepsy, but the opposite is not true.…”
Section: ) Migrainementioning
confidence: 99%
“…Serotonin moreover through various neuropeptides influences on eating behavior, such as orexin-A which is a regulating hormone for appetite and feeding, orexin-A also is related to arousal, reward center, induction of spontaneous exercise (59) so that, in obese women lower serum concentration of orexin-A was seen in comparison with control group (60), interestingly, other correlations between obesity and migraine may be through sleep dis-regulation. In narcolepsy patients which is a sleep disorder determined with orexin-A insufficiency, Both problems are prevalent conditions in narcolepsy patients (61,62).…”
Section: The Association Between Morbid Obesity and Migraine Headachementioning
confidence: 99%
“…Epidemiological studies have shown the presence of a significant comorbidity between migraine and some diseases related to the HLA system, like asthma and narcolepsy [5,6]. This comorbidity suggests the presence, within the HLA region, of genetic factors involved in the disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the CACNA1A and ATP1A2 genes are associated with familial hemiplegic migraine, a rare subtype of migraine with aura [3,4]. The genes involved in the more common form of migraine, like migraine with and without aura, are still unknown.Epidemiological studies have shown the presence of a significant comorbidity between migraine and some diseases related to the HLA system, like asthma and narcolepsy [5,6]. This comorbidity suggests the presence, within the HLA region, of genetic factors involved in the disease pathogenesis.…”
mentioning
confidence: 99%